Estudo da vitrificação dos componentes da argila usada para a fabricação de blocos cerâmicos no município de são Francisco do Oeste/RN - Silva Filho, Mauro José da (Universidade Federal Rural do Semi-Árido, 2017)
Nowadays, most constructions use red ceramics. Clay is the fundamental raw material for making this ceramics and its variability provides the production of several artifacts for various purposes. It is ideal to improve existing production mechanisms or to create new production techniques, directly affecting the quality of the final product, seeking to increase its mechanical strength, durability and compaction of the ceramic material. Based on that, the aim of this essay is to characterize the clay and, by means of a study, verify in the firing phase the ceramic vitrification process, which increases its strength, durability and material compaction, ascertaining which compounds vitrify and at which temperature this process occurs. The research was carried out at Cerâmica Freitas e Chaves, in the Oeste Potiguar region, in the city of São Francisco do Oeste / RN. It was verified that the clay presents high plasticity, demonstrating that the clay is ideal for the ceramics industry and that there is no need for the correction of minerals according to its Plasticity Index. The X - Ray Fluorescence analysis allowed the observation of the chemical elements contents in the studied sample, with the main elements of clay being iron (Fe), silicon (Si), aluminum (Al) and potassium (K), in addition to a high percentage of contaminants. Thus, the study on vitrification enabled to verify that the analysis of the data on clay for the production of red ceramics is ideal because it presents a good rate of vitrification.
Keywords: Argila; vitrificação cerâmica; ensaios de caracterização; produção cerâmica; clay; vitrification of ceramics; characterization tests; ceramics production; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA